A review of the genus Rapala Moore, 1881 (Lepidoptera: Lycaenidae: Theclinae) of Nepal with insights on little-known species - Kc, Sajan; Poel, Piet Van Der; Pariyar, Surendra; Sunar, Aman; Limbu, Mahendra Singh (Zootaxa, 2025)
The taxonomy of Rapala Moore, 1881 in Nepal remains problematic due to historical misidentifications, taxonomic reclassifications, and the absence of comprehensive identification keys. This study reviews Rapala species documented in Nepal based on field observations by the authors, available citizen science data, literature review, and museum specimens. A total of 13 Rapala species are recognized from Nepal under current taxonomy. The historical taxonomic confusion between Rapala rectivitta (Moore, 1879) and R. rosacea de Nicéville, [1889], in Nepal is discussed, with R. rosacea, having previously been considered as R. rectivitta, formally recognized in Nepal’s butterfly fauna for the first time. Additionally, new evidence of R. rectivitta from Nepal is provided. The taxonomic status of R. huangi Nakamura & Seki, 2017 is reaffirmed as valid, warranting its inclusion in Nepal’s faunal list. It is also documented for the first time from NE India. The status of R. hinomaru Fujioka, 1970 is revised; we propose it as a junior subjective synonym of R. nissa (Kollar, [1844]), syn. nov. To facilitate species identification, images of live and spread specimens of all the documented Rapala species in Nepal are provided, along with images of male and female genitalia and dichotomous keys.